Flexible carbon nanofibers for high-performance free-standing supercapacitor electrodes derived from Powder River Basin coal. (15th October 2020) - Wang, Tongtong; He, Xin; Gong, Weibo; Sun, Kaidi; Lu, Wenyang; Yao, Yi; Chen, Zhe; Sun, Tongqing; Fan, Maohong
Abstract: To maximize the utilization of Wyoming sub-bituminous coal and relieve the negative environmental impacts, green synthesis of supercapacitor materials from Powder River Basin (PRB) coal residual were employed to convert coal residuals to high-value carbon materials. The free-standing and binder-free activated carbon nanofibers (ACNFs) were synthesized eco-friendly in CO2 through the carbonization and activation of polyaromatic hydrocarbon-rich extract, which was extracted from the supercritical PRB coal residual by THF Soxhlet. The flexible ACNFs featured various interconnected porous structures endowing the carbon nanofibers (CNFs) with a high specific surface area (743 m 2 g −1 ) and high total pore volume (0.613 cm 3 g −1 ). Moreover, the high-temperature activation in CO2 enhanced the electrical conductivity and reduced the number of oxygen-containing compounds on the surface, which leads to lower charge-transfer resistance. The supercapacitor electrodes prepared from ACNFs have a specific capacitance of 409 F g −1 with some excellent and stable electrochemical performances. Therefore, the green synthesis of supercapacitor electrodes with the extract from PRB coal residuals can expand our horizons for the utilization of low-rank coal.